Changes in Balancing Ability of Athletes With Chronic Ankle Instability After Foot Orthotics Application and Rehabilitation Exercises - Lee, Hong-Jae (Korean Academy of Rehabilitation Medicine, 2013)
OBJECTIVE: To compare the effect of foot orthotics and rehabilitation exercises by assessing balancing ability and joint proprioception in athletes who have chronic ankle instability. METHODS: Forty-one athletes who visited hospitals due to chronic ankle instability were randomly assigned to two groups. One group had ankle rehabilitation exercises while the other group had the same rehabilitation exercises as well as foot orthotics. Joint position sense of the ankle joint was examined by using an isokinetic exercise machine. Balancing abilities categorized into static, dynamic and functional balance abilities were evaluated by using computerized posturography. We tested the subjects before and after the four-week rehabilitation program. RESULTS: After the four-week treatment, for joint reposition sense evaluation, external 75% angle evaluation was done, revealing that the group with the application of foot orthotics improved by -1.07±1.64 on average, showing no significant difference between the two groups (p>0.05). Static, dynamic and functional balancing abilities using balance masters were evaluated, revealing that the two groups improved in some items, but showing no significant difference between them (p>0.05). CONCLUSION: This study found that athletes with chronic ankle instability who had foot orthotics applied for four weeks improved their proprioceptive and balancing abilities, but did not show additional treatment effects compared with rehabilitation exercise treatment.